Correlations among morphological and biochemical traits in high‐cannabidiol hemp (Cannabis sativa L.) - George M. Stack; Craig H. Carlson; Jacob A. Toth; Glenn Philippe; Jamie L. Crawford; Julie L. Hansen; Donald R. Viands; Jocelyn K. C. Rose; Lawrence B. Smart (Plant Direct, 2023)
Abstract Cannabis sativa is cultivated for multiple uses including the production of cannabinoids. In developing improved production systems for high‐cannabinoid cultivars, scientists and cultivators must consider the optimization of complex and interacting sets of morphological, phenological, and biochemical traits, which have historically been shaped by natural and anthropogenic selection. Determining factors that modulate cannabinoid variation within and among genotypes is fundamental to developing efficient production systems and understanding the ecological significance of cannabinoids. Thirty‐two high‐cannabinoid hemp cultivars were characterized for traits including flowering date and shoot‐tip cannabinoid concentration. Additionally, a set of plant architecture traits, as well as wet, dry, and stripped inflorescence biomass were measured at harvest. One plant per plot was partitioned post‐harvest to quantify intra‐plant variation in inflorescence biomass production and cannabinoid concentration. Some cultivars showed intra‐plant variation in cannabinoid concentration, while many had a consistent concentration regardless of canopy position. There was both intra‐ and inter‐cultivar variation in architecture that correlated with intra‐plant distribution of inflorescence biomass, and concentration of cannabinoids sampled from various positions within a plant. These relationships among morphological and biochemical traits will inform future decisions by cultivators, regulators, and plant breeders.